The The Urgency of the Big Book of Digestive System Ethnoscience: An Analysis of the Needs of Reading Interest and Science Literacy of Elementary School Students - Hermansyah; Sri Rahayu Lestari; Hendra Susanto (Yayasan Darussalam Bengkulu, 2026)
This research is motivated by the need for contextual learning media that is able to increase the reading interest and science literacy of elementary school students in the material of the human digestive system. The research aims to analyze the need for the development of Big Books with ethnoscience content as the basis for designing learning media that is relevant to local culture. The research is a preliminary study with a mixed descriptive approach (qualitative and quantitative). The research was carried out in Muruk Rian District, Tana Tidung Regency, North Kalimantan, namely SDN 004, SDN 005, SDN 016, and SDN 024 Tana Tidung, involving 27 students and 4 teachers. Data were collected through observation, science literacy cognitive tests, closed questionnaires, and interviews. The results showed that students' reading interest was relatively high, but there were emotional barriers and uneven reading experiences. The attitude of students' science literacy is positive, but epistemic understanding and involvement in environmental issues is still limited. Students' science literacy skills are in the sufficient category, while procedural skills and scientific inquiry design are relatively low. Teachers and students expressed a high need for contextual and easy-to-understand visual media. These findings confirm the potential of the Big Book containing ethnoscience as a relevant medium to relate science concepts to local culture and become the basis for development and effectiveness testing at the next stage of research.